Forensic science : advanced investigations - Brown, Rhonda M. , 1966-; Davenport, Jackie S. (South-Western Cencage Learning, 2012)
A comprehensive course that offers as a second-level high school course in forensic science, a course area in which students have the opportunity to expand their knowledge of chemistry, biology, physics, earth science, math, and psychology, as well as associate this knowledge with real-life applications.